Efficacy and Safety of Perampanel in Children with Drug-Resistant Focal-Onset Seizures: A Retrospective Review - Ahmed Elmardenly; Zekra Aljehani; Abdullah Tamim; Anas Alyazidi; Osama Muthaffar (MDPI AG, 2023)
Background: Epilepsy is one of the most common neurological disorders. Existing antiseizure medications (ASMs) are still unable to control seizures in one-third of these patients, making the discovery of antiseizure therapies with novel mechanisms of action a necessity. Aim of the Study: This study aimed to determine the safety and efficacy of perampanel (PER) as an adjuvant treatment for children with drug-resistant focal-onset seizures with or without focal to bilateral tonic-clonic seizures. Patients and methods: This is a single-center retrospective study of 38 epileptic pediatric patients, aged 2 to 14, at King Faisal Specialist Hospital and Research Center whose seizures were pharmaco-resistant to more than two antiseizure medications and followed for at least three months after PER adjuvant therapy initiation. Efficacy was assessed by the PER response rate at 3-, 6-, and 12-month follow-up evaluations, and side effects were also reported. Results: Multiple seizure types were reported. Myoclonic seizures were the predominant type of epilepsy in 17 children (44.7%). At 3 months, 6 months, and 12 months of follow-up, approximately 23.4%, 23.4%, and 18.4% of the patients were seizure-free at these time points, respectively. Adverse events were documented in 14 patients (35.7%) and led to the discontinuation of PER in 26.3%, 31.6%, and 36.8% of the studied group at the 3-, 6-, and 12-month follow-ups, respectively. The most common adverse events included dizziness or drowsiness, irritability, gait disturbance, and confusion; however, all were transient, and no serious adverse effects occurred. Conclusion: Our findings confirm the therapeutic efficacy of adjunctive PER in the treatment of drug-resistant epilepsy in children. As an adjunctive treatment for epilepsy, perampanel demonstrated sufficient effectiveness and tolerability.